Identification of Genes Related to Mesocarp Development in Cucumber - Xiaohua Qi; Yamei Zhu; Shuifeng Li; Hanxi Zhou; Xuewen Xu; Qiang Xu; Xuehao Chen (Horticultural Plant Journal, 2020)
Cucumber (Cucumis sativus L.) is an agriculturally and economically important vegetable crop worldwide. The thickness of mesocarp is an important quality pertaining to edibility. The development of mesocarp, however, has received little attention. In this study, we selected one thick mesocarp line D8 to analyze the gene expression profiles of mesocarp at 0, 3, 6, and 9 days after pollination (DAP) by RNA sequencing. Genes mainly related to ribosomes, carbon metabolism, biosynthesis of amino acids, and oxidative phosphorylation were up-regulated at 3 DAP. From 3 to 6 DAP, the genes related to oxidative phosphorylation, photosynthesis, and phagosome were highly induced. From 6 to 9 DAP, the genes related to plant hormone signal transduction were highly induced. Differentially expressed genes linked to cyclin, hormone biosynthesis and signaling, carbon metabolism, and transcription factors MYB and WRKY were common up-regulated at 3, 6, 9 DAP in comparison with 0 DAP. The auxin-responsive and cytokinin-responsive genes were significantly up-regulated in mesocarp development. The higher expression levels of the auxin-responsive gene indole-3-acetic acid-amido synthetase 3.6 and the cytokinin response regulator 3/4b in the thick mesocarp cultivar D8 than in the thin mesocarp cultivar XUE1 might have explained the different growth rates of the mesocarp.